2016
DOI: 10.3390/su8121340
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Urban Food Production and Its Relation to Urban Resilience

Abstract: Food production on the urban-rural fringe is under pressure due to competing land uses. We discuss the potential to improve resilience for urban-rural regions by enhancing food production as part of multifunctional land use. Through studies of peri-urban land in the regions of Gothenburg (Sweden), Copenhagen (Denmark) and Gent (Belgium), recent developments are analysed. Arable farming has been declining since 2000 in all three areas due to urban expansion and recreational land use changes. In city plans, netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 47 publications
0
51
0
3
Order By: Relevance
“…Local municipalities reacted to the loss of these lands by organizing "food councils". However, they concluded that without the implementation of binding policies the agricultural lands will continue to decline [79]. The present case study of Tokyo faces similar challenges.…”
Section: Strategies To Increase Self-sufficiencymentioning
confidence: 91%
See 1 more Smart Citation
“…Local municipalities reacted to the loss of these lands by organizing "food councils". However, they concluded that without the implementation of binding policies the agricultural lands will continue to decline [79]. The present case study of Tokyo faces similar challenges.…”
Section: Strategies To Increase Self-sufficiencymentioning
confidence: 91%
“…Olsson et al (2016) discussed the need to re-couple urban and rural regions food production from a resilience point of view [79]. The European case studies all experienced a reduction in agricultural land uses over recent years within their city regions, consequently reducing food availability.…”
Section: Strategies To Increase Self-sufficiencymentioning
confidence: 99%
“…Traditionally used for agrarian purposes, European rural land has undergone major reshaping in recent decades due to changes in the agrarian and forestry model and the pressures of urbanization and industrialization [1][2][3]. Rural spaces are no longer valued solely for their status as suppliers of agricultural products, but they also offer different alternatives of use, often in conflict with each other.…”
Section: Introductionmentioning
confidence: 99%
“…The public policy approach to multifunctionality in these areas is usually focused on environmental issues that are more likely to be included in planning tools, and perceived as important by local authorities, although social actors also recognise and value other economic and social issues (Vandermeulen et al, 2006;Ives and Kendal, 2013;Marraccini et al, 2013;Olsson et al, 2016).…”
Section: Peri-urban Studiesmentioning
confidence: 99%